ACTS OF LEGAL NORMS INTERPRETATION:: APPROACHES TO UNDERSTANDING AND LEGISLATIVE BASIS - Shevchenko, Anatolii; Antoshkina, Valeriia; Lekhkar, Oksana; Kapichon, Olga (Revista Gênero e Interdisciplinaridade, 2020)
The paper is aimed at determining the concept and legal nature of acts of interpretation; generalization and critical understanding of the legislator’s approaches to determining the role and significance of interpretation acts in the legal system of Ukraine. The main methods for studying the problem are: dialectical, formal-logical, systemic. In particular, the systemic method was used to identify connections and ratio between different acts of interpretation. Based on the analysis of regulatory material, it is concluded that there is no single agreed approach regarding the procedure for issuing interpretative acts, determining their legal force, the procedure for applying and appealing in Ukraine. The authors pay special attention to the lack of legislative regulation of the powers of individual ministries and other agencies to engage in interpretive activities. In their turn, these judicial activities are more streamlined, although they require improvement and modernization. Basing on the analysis of the normative material, the authors outline the main problematic issues regarding the legislative regulation of the question on interpretative acts and make specific proposals for improvement of the existing legislation in that field. The conclusions and suggestions made can be used in the research sphere for further elaboration of problems of legal interpretation, in the sphere of practical activity – while generalizing the legal norms interpretation practice.